Help for the Helper: Mental Health Concerns, Supports, and Stigma in School Counselors. Issue 1 (1st January 2017) - Crowe, Allison; Mullen, Patrick R.; Harris, Janeé R. Avent
Abstract : Self-stigma prohibits many from seeking mental health support, and those in helping professions are not immune to this phenomenon. In this study, we investigated types of mental health concerns, frequencies and types of professional supports, and the relationship between stigma and help seeking in a sample of 330 school counselors. We found significant differences related to gender and familiarity with mental health concerns, as well as differences related to personal experience with mental health concerns. There was no significant difference in stigma for participants who had few personal and professional experiences with mental health concerns and participants who had many professional experiences with mental health concerns.